Efficient Near Infrared Light Triggered Nitric Oxide Release Nanocomposites for Sensitizing Mild Photothermal Therapy. Issue 3 (11th December 2018) - Zhang, Xiao; Du, Jiangfeng; Guo, Zhao; Yu, Jie; Gao, Qin; Yin, Wenyan; Zhu, Shuang; Gu, Zhanjun; Zhao, Yuliang
Abstract: Mild photothermal therapy (PTT), as a new anticancer therapeutic strategy, faces big challenges of limited therapeutic accuracy and side‐effects due to uneven heat distribution. Here, near infrared triggered nitric oxide (NO) release nanocomposites based on bismuth sulfide (Bi2 S3 ) nanoparticles and bis‐ N ‐nitroso compounds (BNN) are constructed for NO‐enhanced mild photothermal therapy. Upon 808 nm irradiation, the high photothermal conversion efficiency and on‐demand NO release are realized simultaneously. Due to the unique properties of NO, enhanced antitumor efficacy of mild PTT based on BNN‐Bi2 S3 nanocomposites is achieved in vitro and in vivo. Mechanism studies reveal that the exogenous NO from BNN‐Bi2 S3 could not only impair the autophagic self‐repairing ability of tumor cells in situ, but also diffuse to the surrounding cells to enhance the therapeutic effect. This work points out a strategy to overcome the difficulties in mild PTT, and has potentials for further exploitation of NO‐sensitized synergistic cancer therapy. Abstract : Nanocomposites based on bismuth sulfide nanoparticles and nitric oxide (NO) donors are constructed to realize simultaneous near infrared‐controlled NO release and mild photothermal therapy (PTT). The results lead to efficient tumor ablation due to the efficient dispersion of NO and the synergistic effect of NO and heat, which could overcome the drawbacks of mild PTT.